The Effect of Over Workload and Role Conflicts on Behavior of Tax Auditor Dysfunction with Working Stress as Mediation Factor and Moral Competence as Moderation Factor: (Empirical study at Indonesian Directorate General of Taxes) - Kencana, Kartika Cahya; Widhiastuti, Susanti (School of Accountancy, University of Agung Podomoro, 2018)
This study examines the theory of transactional processes which applied work stress theory proposedby Gibson et al. (1995). The researcher collected data from tax auditors as participants using surveytechniques by self-filling questionnaires. The qualitative data are converted into the parametric scalewith the Method of Successive Interval and then analysed using Partial Least Square. The result of thisstudy is work stress can mediate the effect of over workload and role conflict on tax auditordysfunction behavior moral competence can not moderate the relationship of influence of work stresson dysfunction behavior. Surveys conducted are not accompanied by researcher in fillingquestionnaires in the theoretical sphere so as to generate potential bias in the results. This studyproduces a quality tax audit of the errors of professional humanism. For further research, can beanalyzed by using the experimental method.